[tex]a) \: 3x - 5 = x + 11[/tex]
[tex]3x - x = 11 + 5[/tex]
[tex]2 x{ = 16} [/tex]
[tex]x = 8[/tex]
[tex]b) \: 2 + 3(x - 1) = 4x - 5[/tex]
[tex]2 + 3x - 3 = 4x - 5[/tex]
[tex] - 1 + 3x = 4x - 5[/tex]
[tex]3x - 4x = - 5 + 1[/tex]
[tex] - x = - 4[/tex]
[tex]x = 4[/tex]
[tex]c) \: \: 3(2x - 1) - 2(x - 2) = 21[/tex]
[tex]6x - 3 - 2x + 4 = 21[/tex]
[tex]4x + 1 = 21[/tex]
[tex]4x = 21 - 1[/tex]
[tex]4x = 20[/tex]
[tex]x = 5[/tex]
[tex]d) \: 5x - 1 = 5(x - \frac{1}{5} )[/tex]
[tex]5x - 1 = 5x - 1[/tex]
[tex]X€R[/tex]